Bentuk dan Konstruksi Pendidikan Politik pada Organisasi Mahasiswa Kesatuan Aksi Mahasiswa Muslim Indonesia (KAMMI) dan Ikatan Mahasiswa Muhammadiyah (IMM) di Kota Pangkalpinang - pratama, imam alfikri (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2022)
This study aimed to find out how, what kind of ways, methods and the political education basic conducted and how the role of political education conducted KAMMI and IMM student organizations in PangkalpinanG. This study used a qualitative approach with descriptive study method. Data collection techniques used were interviews, observation, documentation studies and literature studies. The results revealed that student KAMMI and IMM in Pangkalpinang looked at education as an effort to build political understanding in the context of civilization politics. Besides, the political education could establishing student leadership in managing student organizations. The ways for creating political education are through political education cadre, and training organization; The methods used are training, self-learning, study material, internal discussions and public discussion on the organization. Keywords: Political Education, Student Organization